2020
DOI: 10.3390/nu12113395
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Whether the Mediterranean Dietary Pattern Is Integrated in Routine Dietetic Practice for Management of Chronic Conditions: A National Survey of Dietitians

Abstract: Evidence supports recommending the Mediterranean dietary pattern (MDP) in the management of cardiovascular disease (CVD), type 2 diabetes (T2D), non-alcoholic fatty liver disease (NAFLD) and solid organ transplant (SOT). However, the evidence-practice gap is unclear within non-Mediterranean countries. We investigated integration of MDP in Australian dietetic practice, and barriers and enablers to MDP implementation for chronic disease management. Dietitians managing CVD, T2D, NAFLD and/or SOT patients (n = 182… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 60 publications
(71 reference statements)
1
22
0
Order By: Relevance
“…In particular, they highlighted that educational resources, such as mobile phone apps that offer visual content, clear, concise messages and tips (e.g., recipes, menu plans, food swaps) would facilitate the understanding of specific DP concepts by patients. This agrees with a recent study reporting that dietitians would welcome patient education materials that are visually appealing, user friendly and contain recipes, information on low‐cost alternatives and tips for practical adaptation to current eating habits 24 . Because the integration of nutrition apps in dietetic practice is high, 25 delivery of DP resources through well‐designed smartphone apps might facilitate advice provision and patient take‐up of the advice 26 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, they highlighted that educational resources, such as mobile phone apps that offer visual content, clear, concise messages and tips (e.g., recipes, menu plans, food swaps) would facilitate the understanding of specific DP concepts by patients. This agrees with a recent study reporting that dietitians would welcome patient education materials that are visually appealing, user friendly and contain recipes, information on low‐cost alternatives and tips for practical adaptation to current eating habits 24 . Because the integration of nutrition apps in dietetic practice is high, 25 delivery of DP resources through well‐designed smartphone apps might facilitate advice provision and patient take‐up of the advice 26 .…”
Section: Discussionsupporting
confidence: 87%
“…This training should also incorporate education on DPs, to enhance dietitians’ confidence in providing DP advice. Indeed, several participants in the present study would welcome further training to deliver advice on specific DPs, such as the low‐carbohydrate diet, and earlier research showed that dietitians thought professional development would enable them to provide advice on the MD 24 …”
Section: Discussionmentioning
confidence: 91%
“…Patient education resources based on MDP assisted education and goal setting, while sharing these with multidisciplinary colleagues facilitated MDP recommendations. Developing educational tools for patients and other clinicians has been shown to facilitate dietitians actively seeking and reading the scientific literature (31) , and dietitians have indicated that greater access to practical education resources for patients would facilitate MDP implementation in their practice (18) . Dietitians in the current study described that involvement in developing education resources had supported their MDP knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
“…Martínez–González et al [ 17 ] have also outlined a number of practical approaches which could be adopted by non-Mediterranean populations in order to shift a Western-style dietary pattern to a more Mediterranean-style diet. Nevertheless, in a recent national survey of Australian Dietitians, Mayr et al [ 65 ] reported a lack of patient education resources, including practical and culturally appropriate low-cost recipe options for diverse patient groups as an important practice-related barrier for practitioners. However, implementing change to dietary and lifestyle behaviours, particularly in patients with chronic disease, is indeed complex and is likely to benefit from multi-disciplinary management in order to facilitate behavioural change [ 66 ].…”
Section: Discussionmentioning
confidence: 99%